Charge compensation weakening ionized impurity scattering and assessing the minority carrier contribution to the Seebeck coefficient in Pb-doped Mg3Sb2 compounds. Issue 13 (19th March 2020) - Zhang, Qiang; Hou, Jichong; Fan, Jianfeng; Chen, Shaoping; Fan, Wenhao; Zhang, Hua; Wang, Wenxian; Wu, Yucheng; Xu, Bingshe
Abstract : Charge compensation weakens ionized impurity scattering and increases mobility, and the minority carrier contribution to α is quantified by | α p σ p / α n σ n |. Abstract : This work reports the electrical and thermal transport processes in p-type Pb-doped Mg3(1+ x ) Sb2− y Pb y (0.02 ≤ x ≤ 0.08; 0 ≤ y ≤ 0.02) compounds. Low-energy electron acceptor defects Mg vacancies are easy to form, which can provide holes and make p-type transport in the Mg3 Sb2 matrix. However, with an increase in excess Mg, the transport behavior changes from p type to n type as manifested synergistically by both the Hall coefficient and Seebeck coefficient. This indicates the effective role of Mg in tuning carrier type and concentration for a pristine Mg3 Sb2 compound. Upon substitution of Sb by Pb, the hole concentration slightly increases, and mobility is greatly improved by 133% at room temperature. The significant increase in mobility is attributed to the weakening ionized impurity scattering, stemming from the decreasing concentration induced by Pb doping. Thus, the power factor is enhanced with a 146% improvement at room temperature. Consequently, the figure of merit ZT of the Pb-doped sample is 1.8 times larger than the pristine one at around 300 K. Moreover, the non-degenerate transport behavior revealed by electrical properties is simply analyzed regarding the effects of minority carriers on the overall Seebeck coefficient. This study proposes a new strategy of charge compensation for improving mobility and a simple way to guide the prediction about the onset of bipolar conduction for Mg3 Sb2 -based compounds and other potential thermoelectric materials.